Evolução de um sistema laguna-barreira da formação Rio Bonito, no sul da Bacia do Paraná - Candido, Mariane (Universidade do Vale do Rio dos Sinos, 2016)
This study aimed to construct and interpret a computational model for a particular lagoon-barrier system of the Rio Bonito Formation in Paraná Basin, located in the coalfield Iruí Central. This paper also presents a literature review of the geological depositional environments of interest, especially the lagoon barrier systems, and other relevant concepts for the conception of it. The main goal of this research was to understand the formation and evolution of this system, considering the relative sea level variations. Data were obtained from 75 logged boreholes, with 19 cores distributed along two geological sections, parallel and perpendicular to the paleoshoreline in order to characterize the lagoon-barrier system, and the other to scale the main coal bed deposited behind the barrier. Through the 3D stratigraphic modeling DIONISOS® (Diffusive Oriented Normal and Inverse Simulation of Sedimentation) software, the basic parameters have been established and various data settings simulated. The described facies were interpreted as swamp, lagoon, sandy barrier and tide-influenced deposits. The evolution of this system during the transgressive system tract showed migration of the barrier landward, and during the highstand system tract the migration occurred seaward. A relative sea level rise of about 16 m allowed a strong correlation with data exhibited by the stratigraphic sections along 2 Myr. The past environmental conditions rebuilt through the model, made possible the establishment of the relative sea level curve and the likely locations of sediment supply in this environment, allowing better inferences about the evolution steps of this existing system in the Rio Bonito Formation.
Keywords: Sucessão do depósito carbonoso; Modelagem estratigráfica; Transgressão da barreira; Coal bearing succession; Stratigraphic modeling; Barrier transgression; ACCNPQ::Ciências Exatas e da Terra::Geologia